Mediação de conflitos no Sistema Único de Saúde: visões e práticas de uma experiência no município de Natal/RN - Silva, Adriana Torquato da (2016)
In Brazil of the twenty-first century, twenty seven years after the promulgation of the Constitution, the achievement of fundamental social rights it is challenging, where par excellence, is the right to health. The growing demand of citizens to full health care promised by the Constitution of 1988, highlighted by the difficulties between the constitutional promised and the political, administrative and financial capacity of the Brazilian State to fulfill it. Citizens who do not find the answer to your attention needs actions and health services networks seek, through the judiciary intervention, the solution to your problem, which has resulted in a phenomenon called "Legalization of Health." Parallel to this phenomenon other situation was confirmed: the difficulties of the justice system in dealing with social rights. The model of justice shows to be incompatible with the urgent nature involving lawsuits in Health, challenging the creativity of legal professionals, health professionals and managers in the search for alternative solutions to deal with the complexity of the issue. This research aimed to analyze the social technology of mediation applied to the phenomenon of legalization of health as an extrajudicial settlement of conflicts, from the experience of SUS MEDIATED NATAL Program. The research, in its qualitative approach, accomplished documentary analysis of the Program records and interviews with people involved in the same - Law operators, representatives of the Magistracy, technical colaborators and SUS program managers, the municipal and state sphere. The study period included the years 2012 to 2014. This was a profile and referrals made during the period studied, in relation to quantitative consultations, agreements, actions proposed by the DPE, referrals actions to DPU, resoluteness index and demands index not filed against state and county, and perceptions about the practices experienced by the people involved. The results showed that the perceptions of people linked to the field of Law and Health are contradictory as to the legalization of health phenomenon, between negative and positive aspects. In regards to the creation and development of the program SUS MEDIATED NATAL, there was a consensus that it helped to realize the rights to health. As far as the mediation, similar views were identified considering that it is an appropriate tool to deal with the legalization, because it reduces the number of actions proposed in the Judiciary, directs better the competence of the federative while searching the administrative resolution of the cases. It was noted that the problems that pervade the mediation are much the same identified in the operation of the Health System: insufficient offers, difficulty of access to new technologies, deficit and need for better training of human resources, difficulties in the organization of work processes. It is concluded that for these issues neither the legalization nor mediation will provide a resolute response. It is considered, finally, the educational potential of mediation as an important contribution of the Program, as the dialogue on the health system issues allow the user orientation and at the same time, positively discloses SUS to the citizen, reconciling it with the health system. This communication is expensive to SUS and can contribute simultaneously to the optimization of Justice and Health Management, and advances in citizenship and the affecteviness of social rights.